2018
DOI: 10.1097/md.0000000000010134
|View full text |Cite
|
Sign up to set email alerts
|

Decreased functional connectivity and structural deficit in alertness network with right-sided temporal lobe epilepsy

Abstract: Patients with temporal lobe epilepsy (TLE) often suffer from alertness alterations. However, specific regions connected with alertness remain controversial, and whether these regions have structural impairment is also elusive. This study aimed to investigate the characteristics and neural mechanisms underlying the functions and structures of alertness network in patients with right-sided temporal lobe epilepsy (rTLE) by performing the attentional network test (ANT), resting-state functional magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…However, this correlation is only significant considering all subjects (and in some cases, only subjects from the control group), showing that it is group-unspecific. A study showed significant correlation between impulsivity and ADHD scores in typical adults with higher-volume anatomic asymmetry in the right caudate nucleus compared to the left, thus emphasizing the dimensional character of phenomena related to control mechanisms of the motor behavior [28]. Similar anatomic asymmetry has also been observed in children with ADHD [4–6].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, this correlation is only significant considering all subjects (and in some cases, only subjects from the control group), showing that it is group-unspecific. A study showed significant correlation between impulsivity and ADHD scores in typical adults with higher-volume anatomic asymmetry in the right caudate nucleus compared to the left, thus emphasizing the dimensional character of phenomena related to control mechanisms of the motor behavior [28]. Similar anatomic asymmetry has also been observed in children with ADHD [4–6].…”
Section: Discussionmentioning
confidence: 84%
“…It has been suggested that the activity on the left, associated to phasic alertness, would correspond to selective voluntary attention mechanisms triggered by attention modulation sustained by the warning signal [56]. However, recent studies on brain changes caused by lesions [28], with functional neuroimage [27], and ERPs with repetitive transcranial magnetic stimulation [26] have also suggested the participation of the right hemisphere in phasic alertness, clearly showing that the model for this attentional network is still not definitive. Our findings corroborate the participation of the right hemisphere in phasic alertness, and suggest that its mechanisms would be corrupted in ADHD, which could be a substrate for behavioral differences found between the groups regarding of the efficiency of the alerting network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right IPL is crucial in the DMN and the frontal parietal network, participating in sustaining attention, alertness, and task switching. Studies in rTLE using resting state fMRI, found that the right IPL had lower functional connectivity (FC) in TLE when compared with the control group ( 14 , 67 ), which might result in alertness impairment in patients. Because the parietal lobe is connected to the temporal lobe, epileptic discharges from the epileptogenic zone (right temporal lobe) can spread to distant brain regions through the superior longitudinal fasciculus.…”
Section: Discussionmentioning
confidence: 99%
“…Thalamus has been shown to be related to emotional regulation. [ 40 ] The PCC is implicated in different key cognitive and behavioral functions, such as self-processing consciousness and executive function. [ 41 , 42 ] In this work, we found a reduced FC of MOFG in treatment-naive, first-episode MDD patients.…”
Section: Discussionmentioning
confidence: 99%